PENERAPAN VIDEO PEMBELAJARAN UNTUK PENINGKATAN HASIL BELAJAR SISWA SMK MUHAMADIYAH 01 PADANG - Wiwita, Risma; Efendi, Efendi; Melshandika, Yolla (Jurnal Manajemen Pendidikan, 2022)
That with the spread of the covid-19 virus, the teaching and learning process has turned into distance learning to limit the spread of the covid 19 virus. Online distance learning began in early March 2020. This requires educators to think about what methods and media will be used. used for the teaching and learning process. For this reason, learning videos (Youtube) are used in the classroom teaching process. The purpose of this study was to improve learning outcomes by applying learning videos (Youtube) in Class X TKJ 1 SMK Muhamadiyah 1 Padang. Based on the data analysis of the first cycle to the second cycle there is an increase in learning outcomes. The average student learning outcome in the first cycle was 82.57 with a percentage of 72.73%. At the end of the second cycle learning outcomes increased to 87.45 with a percentage of 91.34%. The minimum completeness standard in this study is 80 and the research indicator is determined that 80% of students complete above the SKM. In this study, there were 91.34% of students above the SKM. Based on the results of this study,the teachers in the field studies can use learning videos for online learning.